A Framework for Indigenous Adoptee Reconnection: Reclaiming Language and Identity. - Sarah Wright Cardinal (Canadian Society for Studies in Education, 2016)
Canadian society is ascribing increasing importance to the large numbers of Indigenous children who have - and continue to live - in the child welfare system. An unexplored aspect of this phenomenon is how such children rebuild their Indigenous identities once they become adults and are no longer in care. Recent estimates suggest up to 20,000 First Nations, Metis, and Inuit children were removed from their families during what was known as the Sixties Scoop (Sixties Scoop Survivors, 2015). The Sixties Scoop is part of Canada's colonial story in which the prevalent assimilative force has been disconnecting Indigenous children from their families and understandings of the world. To date, there is little research on how transracially adopted Indigenous adults reconnect with their Indigeneity. Identity reclamation is a personal and intimate process. I begin by summarizing the scholarly literature on the Sixties Scoop, and describe a proposed theoretical framework of Indigenous adoptee identity reclamation emerging from my reflexive process in writing a critical personal narrative. I emphasize the importance of shifting from 'othering' hegemonic discourses to a spirit-based discourse of healing and wholeness. Finally, I engage in a broader dialogue on decolonizing education from Indigenous perspectives.